A Modified Structural Setting and Subsurface Distribution of Cretaceous Facies from Southwest to Northeast in The Calabar Flank of The Lower Benue Trough - Selema, S. B.; Acra, E. J.; Ideozu, Richmond (European Journal of Applied Sciences, 2023)
This research is focused on the structural setting and subsurface distribution of cretaceous facies in the Calabar Flank, Lower Benue Trough. The aim of this research is to compare the works of Nyong (1995), Reigers and Petters, (1997) in light of new available subsurface data. Materials used are data sets from three wells drilled at different periods within the same acreage (Wells A, B and C). Seismic data, well logs and mud log data have been used to analyze and study the subsurface geology of the study area. Well data from the three wells were viewed and matched with processed seismic data. A composite stratigraphic section produced show correlatable facies, their lateral extents and the subsurface facies distribution in the study area. Well A drilled, south central Calabar Flank encountered shale and sandstone, very thick shale unit with limestone overlying sandstone at the base. Well B also drilled south central Calabar Flank about 0.8km from Well A encountered the same sequence. Whereas Well C drilled about 4.7km from Well B encountered sandstone, shale, marlstone and limestone. This research shows that only well C encountered marlstone. Observations from the well sections, show the penetrated limestone unit appears disconnected, with very high resistive anomaly suggesting that the limestone reservoir penetrated by the three wells are not laterally continuous. These findings tend to modify the earlier published articles on the structural setting and subsurface distribution of Cretaceous sediments SW to NE of the Calabar Flank South Eastern Nigeria in terms of facies distribution, facies lateral extent and structural variability or changes.